The influence of intravenous solution «Neoreodez» on the course of experimental endotoxemia and evaluation of the regenerative properties of drug in the conditions of application. - Mamchur, V. I.; Dronov, S. M.; Bilenkyi, G. Z. (Medicni Perspektivi, 2016)
In the experiment it was shown that experimental endotoxemia induced by introduction of carbon tetrachloride and bacterial lipopolysaccharide is characterized by activation of free radical oxidation and failure of antioxidant defense system. Intravenous injection of solution «Neoreodez» under these experimental conditions has a positive impact on the course of endogenous intoxication, which is manifested by decrease in the concentration of MDA and DC in the liver on average by 1½ times (p≤0.05), decrease in the level of AlAT and AsAT serum by 2 times (p≤0.05) and to restore the balanced functioning of antiradical protection – increased activity of SOD by 1.6 times (p<0.05) in comparison with the performance of the active control. It is established that two-week application «Neoreodez» of solution potentiate the processes of natural reparation of damaged skin.